Statistical analysis of a Tagore song based on Raga Kafi - Chakraborty, Soubhik; Singh, Prerna (Journal of AppliedMath, 2023)
Rabindra Sangeet or Tagore songs encompass a wide variety of human emotions. Most of these songs are based on Hindustani ragas. Kafi is a joyful raga and therefore could be helpful to combat stress. We are motivated to analyse a popular Tagore song, namely, Momo Chitte, which is based on this raga. Statistical analysis compares two phases of 30 s each of a vocal recording of this song. Several statistical features are considered including note duration, inter onset interval, rate of change of pitch, statistical parameterization of melody and rhythm in addition to analysis of spectrogram and pitch profile. The experimental results are encouraging.